Developing Digital L2 Literacy During Compulsory Schooling - Cariaga, Romina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This reflection article analyzes a pedagogical experience, carried out at a public secondary school in Argentina, in an English course. Its goal was to develop students’ digital L2 literacy through collaborative digital storytelling, making students aware of the significant role that multimodality plays in communicating messages. The methodology chosen was ‘project work’ as a teaching strategy. The project’s teaching sequence was made up of five phases: bibliographical research,design, video production, socializing and assessment. The conclusions presented stem from the systematic use of participant observation technique, based on the analysis of multiple data sources (classroom discussions, students’ writing of drafts, final video products and post-project selfevaluation). They show that the experience provided students the opportunity to develop digital literacy, a key competence for the 21st Century which should become the very core of what L2 teachers should focus on these days.